Former aux compétences interculturelles en école d’ingénieur - Marc Weisser (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In a globalized economy, working as an engineer requires to be open to various intercultural phenomena as typically encountered through both production management tasks and international or business relationships. The purpose of this article is to expose ideas on how to provide training to these expected intercultural skills within the framework of engineering schools. At first, the link between culture and interculturality is investigated, showing the role of argument which is assigned to cultural features deriving from a language interaction. By combining French national training standards with the related discussions conducted by the European Council, the intercultural skills needed by tomorrow engineers are further characterized. Finally, two dedicated training methods are proposed, taking into account both the targeted audiences and the features of university pedagogy (i.e. critical incident learning and problem-based learning).